P13 Communicating needs and features of IBD experiences (CONFIDE) survey: patient and health care professional perspectives. (19th June 2022) - Redondo, Isabel; Rubin, David; Panaccione, Remo; Bleakman, Alison Potts; Kayhan, Cem; Atkinson, Christian; Gibble, Theresa Hunter; Ellis, Hilary; Healey, Kristine; Shan, Mingyang; Hibi, Toshifumi; Chaudhury, Koyel
Abstract : Introduction: Communicating Needs and Features of IBD Experiences (CONFIDE) aims to further understand the experience and impact of symptoms on patients' (pts') lives and elucidate any gaps in communication between healthcare professionals (HCPs) and pts with moderate-severe ulcerative colitis (UC) and Crohn's disease (CD) in the US, Europe, and Japan. These data focus on US UC pts and HCPs. Methods: An online, quantitative, cross-sectional survey was conducted on HCPs (n=200) and pts with moderate-severe UC (using criteria from previous treatment experience, steroid use and/or hospitalization) (n=200) in the US between May (HCPs) and July (pts) 2021. The HCP survey included physicians (89%) and non-physician HCPs (11%) responsible for making prescribing decisions. Results: The top 3 symptoms currently and ever suffered by pts (mean age: 40.4, 61.5% male) were diarrhea (62.5% and 74.0%), bowel urgency (47.0% and 61.5%), and increased stool frequency (38.5% and 57.5%). Blood in stool was reported by 27.0% pts as currently suffering, and 51.0% ever. Per HCPs (78.0% male), the top 3 pt-reported symptoms were diarrhea (73.5% ranked in top 3), blood in stool (69.0%), and increased stool frequency (37.5%). 24.0% HCPs reported bowel urgency in the top 3 pt-reported symptoms. Pts self-rated their disease severity as 10.5% (n=21) mild UC, 71.0% (n=142) moderate UC, 17.5% (n=35) severe UC, and not known 1.0% (n=2). Bowel urgency was more frequent with severe UC (62.9%, n=22) than mild-moderate UC (42.9%, n=70). 76.5% (n=153) pts were receiving advanced therapies; 46.4% currently experiencing bowel urgency. Only 38.2% pts felt comfortable reporting bowel urgency to their HCP, while 62.2% (n=23) reported feeling embarrassed talking about it. 75.5% (n=151) HCPs reported they proactively discussed bowel urgency at appointments. HCPs not proactively discussing bowel urgency (24.5%, n=49) expect the pt to bring it up (46.9%, n=23). Conclusions: Bowel urgency is the second-most commonly reported symptom by moderate-severe UC pts, but is not among the HCP-perceived top 3. A substantial proportion of moderate-severe UC pts receiving advanced therapies continue to report bowel urgency. Communication gap between pts and HCPs was identified and highlights the under-appreciation of bowel urgency as an important symptom impacting pts' daily life.